Phylogenetic relationship, biogeography, and conservation genetics of endangered Fraxinus chiisanensis (Oleaceae), endemic to South Korea - Changkyun Kim; Dong-Kap Kim; Hang Sun; Joo-Hwan Kim (Plant Diversity, 2022)
Endemic plants are important for understanding phylogenetic relationships, biogeographical history, and genetic variation because of their restricted distribution and their role in conserving biodiversity. Here, we investigated the phylogenetic relationships of the Korean endemic Fraxinus chiisanensis by reconstructing the molecular phylogeny of Fraxinus based on two nuclear DNA (nrITS and phantastica) and two chloroplast DNA (psbA-trnH and rpl32-trnL) regions. Within our fossil-calibrated phylogenetic framework, we also inferred the biogeographical history of F. chiisanensis. To provide a scientific basis for the conservation of F. chiisanensis, we determined the levels of genetic diversity and genetic differentiation in this species. Combining information from nuclear and chloroplast DNA sequence data, our molecular phylogenetic analyses identified F. chiisanensis as a genetically distinct unit from its sister group, Fraxinus platypoda from Japan. Our molecular dating analyses using nuclear and chloroplast DNA data sets show F. chiisanensis diverged from its sister F. platypoda in the Early or Middle Miocene and differentiated in the Late Miocene on the Korean Peninsula. Our results suggest that the divergence of F. chiisanensis was associated with the submergence of the East China Sea land bridge and enhanced monsoons in East Asia. When compared to F. platypoda, F. chiisanensis exhibits low genetic diversity within populations and high genetic differentiation among populations. These results help us to understand the evolutionary history of F. chiisanensis and to develop a conservation strategy for this species.